Analysis of an Airfoil with Rotating Cylinder for Improved Performance - Al-Abdullah, Anfal (2019)
A Master of Science thesis in Mechanical Engineering by Anfal Al-Abdullah entitled, “Analysis of an Airfoil with Rotating Cylinder for Improved Performance”, submitted in April 2019. Thesis advisor is Dr. Mohammad Omar Hamdan and thesis co-advisor Dr. Muhammad Imran Qureshi. Soft and hard copy available.